What about the Antibacterial Activity of Fresh Ginger Juice (Zingiber officinale)? - Goncagül, Gülşen; Güceyü, Çi̇ğdem; Kardoğan, Özlem; Günaydin, Elçi̇n (Sciencedomain International, 2021)
Background: The aim of this study was to determine the antibacterial activity of the juice obtained by squeezing fresh ginger roots (Zingiber officinale) against the standard strains Staphylococcus aureus (ATCC® 25923) and Escherichia coli (ATCC® 25922), as well as Acinetobacter baumannii and Klebsiella pneumoniae isolated from patients hospitalized in intensive care units.
Methods: For this purpose, the antibacterial effect of the fresh ginger juice was tested against antibiotics such as ampicillin, cefazolin, cefuroxime, meropenem, colistin, ofloxacin, sulfamethoxazole/trimethoprim, tetracycline, and gentamicin. The antibacterial effects against the tested bacteria were determined by the disc diffusion method using 5 µL, 10 µL, 15 µL and 20 µL amounts of ginger juice impregnated on sterile discs.
Results: As a result of the study, it was detected that the antibacterial effect increased in parallel with the increasing amounts of fresh ginger juice in all tested bacteria.
Conclusion: Consequently, fresh Zingiber officinale can provide protection to a certain extent against bacterial pathogens due to its antibacterial action.
Keywords: 6. Clean water; 3. Good health